Pengaruh Terapi Reiki terhadap Kecemasan pada Orang dengan HIV/AIDS (ODHA) - I Nengah Sumirta; AA Sri Sasmita Laksmi; I Wayan Candra; IGA Harini; IDM Ruspawan (Jurnal Gema Keperawatan, 2020)
This study attempts to prove the influence of anxiety ODHA Reiki Therapy .Using research pre experimental design with the kind of research one-group pre-post test design .Data collection with simple random sampling , the large sample 16 .Measuring anxiety T-MAS use .Data analysis with Wilcoxon Test Range , show any impact Reiki Therapy to anxiety ODHA with p value 0,017 on 5% significance.